Firm Performance: Exploring International Diversification, Financial Leverage, and Board of Directors in the Energy Sector - Ath Thaariq, Sundoro; Pangestuti, Dewi Cahyani (Jurnal ASET (Akuntansi Riset), 2024)
This study examines the impact of international diversification, financial leverage, and board composition on the performance of energy sector companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. Using panel data regression with the Random Effects Model (REM), the analysis includes data from 54 energy companies over a five-year period, resulting in 270 observations. The findings indicate that international diversification does not exert a significant influence on firm performance. Conversely, financial leverage has been demonstrated to exert a deleterious influence on firm performance. Furthermore, the size of the board of directors was found to have no significant impact on firm performance. These findings underscore the necessity for energy sector companies to prioritize core business operations, exercise financial responsibility, and enhance governance practices. By integrating variables that are typically studied separately, this study offers new insights into the determinants of firm performance in the energy sector. The research offers a novel theoretical perspective by combining international diversification, financial leverage, and board composition into a single analytical framework, thereby addressing a gap in the existing literature.  To further develop these findings, future research should investigate additional variables, such as macroeconomic conditions and government policies, in order to gain a more comprehensive understanding of the factors that influence firm performance in the energy sector.